3D Analyses of crack propagation in torsion - D. Shiozawa; I. Serrano-Munoz; S. Dancette; C. Verdu; J. Lachambre; J.-Y. Buffiere (Fracture and Structural Integrity)
The initiation and propagation of fatigue cracks during cyclic torsion loading was studied in a cast Al alloy (A357) with a relatively large (~500 μm) grain size. 2D observations, revealed that multi site crack initiation occur on the {111} slip planes exhibiting the highest slip activity (iso-strain Taylor analysis), preferentially on planes nearly perpendicular to the sample axis. Within the first grain, the cracks have a pronounced crystallographic propagation mode (mode II crack growth) and strongly interact with the grain boundaries. In situ 3D monitoring of torsion fatigue tests using synchrotron X-ray tomography reveal that propagation towards the interior of the samples occurs first along the sample periphery in mode II leading to relatively shallow cracks which penetrate towards the sample center only after a large number of cycles is reached .The values of mode I, II and III stress intensity factors have been calculated from finite element simulation at the tip of the shallow mode II crack. Those values are used to analyse the bulk propagation of the observed cracks.